2019
DOI: 10.37695/pkmcsr.v2i0.454
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Malnutrition Problem By Increasing Nutritional Awareness In Desa Pagedangan

Abstract: Children malnutrition is a crucial problem in developing countries including Indonesia. The root main cause of malnutrition is due to the lack of educational background and low economical condition, resulting in inadequate protein intake that still below the Recommended Dietary Allowance (RDA). It was recorded that 6.89% of children under five years old suffered from malnutrition in Desa Pagedangan, Tangerang Selatan. To overcome this problem, community service was conducted to increase nutritional awareness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been found that tempe flour-based products have higher flavonoid content than wheat-based products ( 14 ). Because of its high glutamic acid and protein content, overripe tempe is utilized both as a source of umami flavor and protein in porridge for children under five years old to help overcome children’s malnutrition ( 15 ). Recent research has also proven that tempe application as yogurt has higher antioxidant, carbohydrate, protein, and lipid content compared with plain cow milk yogurt, thus it is being mass-produced ( 16 ).…”
Section: Soy-based Tempe In Generalmentioning
confidence: 99%
“…It has been found that tempe flour-based products have higher flavonoid content than wheat-based products ( 14 ). Because of its high glutamic acid and protein content, overripe tempe is utilized both as a source of umami flavor and protein in porridge for children under five years old to help overcome children’s malnutrition ( 15 ). Recent research has also proven that tempe application as yogurt has higher antioxidant, carbohydrate, protein, and lipid content compared with plain cow milk yogurt, thus it is being mass-produced ( 16 ).…”
Section: Soy-based Tempe In Generalmentioning
confidence: 99%